ANALISIS KEMAMPUAN PENALARAN MATEMATIS VOLUME BANGUN RUANG PADA SISWA KELAS 5 SD 3 GOLANTEPUS - Amaliyah, Fitriyah (JRPD (Jurnal Riset Pendidikan Dasar), 2024)
Mathematical reasoning ability is an important ability for students to solve problems.This study aims to analyze students abilities in using mathematical reasoning as a basis for implementing and improving concepts and methods of teaching mathematical reasoning. This study is a qualitative study with a descriptive exploratory method. The subjects of the study are 24 students from 5th grade at SD 3 Golantepus, Mejobo, Kudus. Data collection techniques include observation, written tests, and interviews. The written test consists of 5 essay questions about the volume of three-dimensional shapes in mathematics. The questions were designed based on indicators of mathematical reasoning ability, which include presenting mathematical statements in writing, diagrams, and drawings, making conjectures and performing mathematical manipulations, organizing and justifying the correctness of solutions, and drawing conclusions. The students work was then assessed using a rubric for evaluating mathematical reasoning ability, and the results were categorized into levels of students' mathematical reasoning abilities. The findings show that 12,5% of students from 5th grade at SD 3 Golantepus fall into the high category, 70,8% into the medium category, and 16,7% into the low category. This indicates that most students have a good level of understanding in mathematical reasoning